Effect of carbon fibers grafted with carbon nanotubes on mechanical properties of cement-based composites. (30th August 2018) - Cui, Hongzhi; Jin, Zhiyang; Zheng, Dapeng; Tang, Waiching; Li, Yubo; Yun, Yanchun; Lo, Tommy Yiu; Xing, Feng
Highlights: A novel chemical method was developed for grafting CNTs onto the surface of CF using KH550. The CNTs were grafted onto the surface of CF through SiOSi bond formation. A large number of CNTs were uniformly and densely distributed on the surface of CF. Cement pastes with CF-CNTs can improve the strengths of cement paste 40% higher than the pure cement paste. Abstract: In this study, a novel chemical method was developed for grafting carbon nanotubes (CNTs) onto the surface of carbon fibers (CF) using (3-Aminopropyl) triethoxysilane (KH550). The CNTs with carboxyl groups and oxidized CF (O-CF) were modified by KH550 before the grafting procedure. The CNTs were grafted onto the surface of CF through SiOSi bond formation due to the hydrolysis and self-condensation reactions of KH550. The effects of CNTs grafted CF (CF-CNTs) on mechanical properties of cement-based composites were studied and compared with composites containing oxidized CF and raw CF. The morphology and chemical structure of CF-CNTs composites were characterized by Scanning electron microscopy (SEM), Laser Raman Spectrometer (LRS), Transmission electron microscope (TEM), Fourier Transform Infrared Spectrometer (FTIR) and X-ray photoelectron spectroscopy (XPS). The test results indicated that a large number of CNTs were uniformly and densely distributed on the surface of CF. The results also indicated that the CNTs and CF were held together by strong chemical bonds. When 0.5 wt% CF-CNTs was added, the flexural strength values of cement pastes at 3d, 7d and 28d were higher than those of pure cement paste and cement pastes containing same content of oxidized CF by 48.5%, 42.2% and 45.5% and 20.7%, 14.6% and 21.5%, respectively. However, the addition of CF-CNTs had little effect on the compressive strength of cement.